2017
DOI: 10.1002/rmv.1961
|View full text |Cite
|
Sign up to set email alerts
|

An overview: Rabbit hepatitis E virus (HEV) and rabbit providing an animal model for HEV study

Abstract: SummaryHepatitis E virus (HEV) is a single-stranded, positive-sense RNA virus and the causative agent of hepatitis E. The virus belongs to genus Orthohepevirus in the family Hepeviridae, which contains 4 major genotypes closely relating to humans. Genotypes 1 and 2 only infect humans whereas genotypes 3 and 4 HEV are harbored in a wide range of animal species worldwide and are zoonotic to humans. Recently, a novel animal strain of HEV has been isolated in farmed rabbits in China, and subsequently more strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 53 publications
(89 reference statements)
0
33
1
Order By: Relevance
“…To better classify these three new strains, a phylogenetic analysis was performed. As based on the HEV reference sequences proposed by Smith et al [ 15 ] and used by others [ 28 , 29 , 33 , 35 ], 81 complete genomes of Orthohepevirus A species were retrieved from the GenBank database ( S2 Table ), including 11 HEV-1, 1 HEV-2, 22 HEV-3, 22 rabbit HEV, 17 HEV-4, 1 HEV-5, 2 HEV-6, 2 HEV-7, and 3 HEV-8 strains. A phylogenetic tree was constructed using the 81 reference sequences and the genomes of DLS13-11677, DLS13-11681, and DLS13-11685 ( Fig 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To better classify these three new strains, a phylogenetic analysis was performed. As based on the HEV reference sequences proposed by Smith et al [ 15 ] and used by others [ 28 , 29 , 33 , 35 ], 81 complete genomes of Orthohepevirus A species were retrieved from the GenBank database ( S2 Table ), including 11 HEV-1, 1 HEV-2, 22 HEV-3, 22 rabbit HEV, 17 HEV-4, 1 HEV-5, 2 HEV-6, 2 HEV-7, and 3 HEV-8 strains. A phylogenetic tree was constructed using the 81 reference sequences and the genomes of DLS13-11677, DLS13-11681, and DLS13-11685 ( Fig 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Rabbit HEV strains have been found in farmed, wild, pet and laboratory rabbits in China [ 19 , 20 ], the United States [ 21 , 22 ], France [ 23 , 24 ], Italy [ 25 , 26 ], Germany [ 27 , 28 , 29 ], the Netherlands [ 30 ], Korea [ 31 ], and Canada [ 32 ]. Phylogenetic analysis of full-length genomic sequences indicates that all rabbit HEV strains together form a separated clade that is closely related to HEV-3 (76–79% nucleotide identities, excluding the two highly divergent rabbit-derived sequences KJ013414 and KJ013415 with only 72–73% identities), but distant from other genotypes of HEV [ 33 ]. The genomes of all rabbit HEV strains harbor a signature insertion of 93-nucleotides (nt) (31 amino acids) in the X domain of ORF1 that is absent in any other known HEV strains [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, rabbits had been shown to be susceptible to experimental infection by genotype 4 HEV isolates from human and pig animal hosts. Moreover, the advantages of rabbits as an animal model for researching HEV pathogenicity have been described previously (46,47) and include lower cost and easier manipulation than with large animals, prompting the use of rabbits here for in vivo MAb neutralization assays. Notably, our results demonstrated that CHN-SD-sHEV (genotype 4 swine HEV) could cause robust infection of rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, RNA levels might be below the threshold of detection limit of the PCR (see, for example, Germer et al, 2017). Moreover, HEV RNA detection rates are usually lower than those based on anti-HEV antibodies (Wang et al, 2018), making it fairly difficult to identify its circulation, even in large sample sets (e.g. Hammerschmidt et al, 2017;Izopet et al, 2012;Zhao et al, 2009).…”
mentioning
confidence: 99%